Enhanced sensitivity, robust p21 activation, and sustained DNA repair responses to interstrand crosslinks in elephant cells compared to humans - Kitano, Taisuke; Zhu, Zida; Minami, Naoya; Orino, Koichi; Yoshikawa, Yasunaga (Frontiers in Veterinary Science, 2025)
Elephants exhibit remarkable resistance to cancer, and understanding these mechanisms has focused on their potential applications in cancer prevention and treatment in humans. A genome-wide comparative analysis identified that the accelerated regions in elephants are enriched in Fanconi anemia (FA) complementation group L (FANCL), a ubiquitin E3 ligase that mediates the monoubiquitylation of FANCD2 as an essential step in the FA pathway. The FA pathway plays a crucial role in DNA interstrand crosslink (ICL) repair, contributing substantially to genome stability and cancer resistance. In this study, we investigated the differences in ICL repair via the FA pathway, including the function of FANCL, as well as the DNA damage response to ICLs between elephants and humans. We found that elephant fibroblasts exhibited higher sensitivity to ICL-inducing treatments, such as mitomycin C and trimethylpsoralen plus UVA (PUVA), than human fibroblasts, while showing comparable or reduced sensitivity to other DNA-damaging agents, such as doxorubicin and bleomycin. Functional analyses revealed that elephant and human FANCL performed similarly in mediating FANCD2 monoubiquitylation and cell viability following mitomycin C treatment. Interestingly, elephant fibroblasts exhibited a more potent and prolonged activation of p21 and sustained DNA repair responses, such as FANCD2 monoubiquitylation and increased RAD51expression, following ICL-induced treatments. Moreover, elephant fibroblasts showed significantly greater RAD51 foci formation than human fibroblasts after PUVA treatment, even under comparable levels of DNA damage. These findings suggest that elephants efficiently repair ICLs in growth-arrested cells likely through robust p21 activation. This study provides new insights into the cancer resistance mechanisms of elephants and offers novel approaches for cancer prevention and therapy.